Effects of using different materials at interface of trapezoidal reinforced concrete infilled frames–analytical and experimental approaches - Vishali, Mugunth; Bahrami, Alireza; Satyanarayanan, Kachabeswara Srinivasan; Thirumurugan, Varatharajan; Prakash, Murugan (Frontiers in Materials, 2023)
Infilled frames are generally formed by the composite interaction between the frame and the infilled wall used for functional purposes. The composite interaction increases the in-plane lateral stiffness of the frame, which is considered an advantage. However, the interaction also alters the ductile mode of failure to the brittle mode along with the increased base shear owing to its higher stiffness compared with the bare frame. A detailed and comprehensive study of the literature revealed that many of research works have been done on rectangular and square frames, and studies on trapezoidal infilled frames are scarce. In this article, we studied different configurations of reinforced concrete frame structures known as trapezoidal frames, which have higher stiffness than rectangular frames. A trapezoidal frame is used for industrial buildings, and its behavior under a lateral load has already been established for a bare frame. However, the interaction and behavior of the infilled frame were investigated in this research. The behavior of a trapezoidal single-story frame was examined under both lateral loading and various interface materials. One of the most frequently suggested methods for infilled-frame analysis is the equivalent diagonal strut. Effective strut width design recommendations are available for rectangular and square frames but not for trapezoidal frames for macro modeling. Hence, to make the design easier, an effective diagonal width was developed for different interface materials with respect to the relative stiffness of various frame cross-sections, and further validation was conducted with a framework of ideology from biomimicry using the nature of a one-sixth scale model. The effective strut width for the trapezoidal infilled frame varied between d/8 and d/9 for the cement mortar and cork interfaces, where d is the diagonal length of the frame.